Wide vector solitons in systems with time- and space-modulated nonlinearities - Arroyo Meza, L. E. [UNESP]; De Souza Dutra, A. [UNESP]; Hott, M. B. [UNESP] (American Physical Society (APS), 2013)
In this work we apply point canonical transformations to solve some classes of two coupled nonautonomous nonlinear Schrödinger equations with specific cubic and quintic - time- and space-dependent - nonlinearities. The method applied here allows us to find a class of wide localized (in space) vector soliton solutions of nonautonomous nonlinear Schrödinger equations. The vector solitons found here can be applied to theoretical studies of Bose-condensed atoms in two different internal states and of ultrashort pulse propagation in optical fibers with focusing and defocusing nonlinearities. © 2013 American Physical Society.